2022
DOI: 10.1093/ofid/ofac656
|View full text |Cite
|
Sign up to set email alerts
|

Short Course of Antifungal Therapy in Patients With Uncomplicated Candida Bloodstream Infection: Another Case of Less Is More in the Clinical Setting?

Abstract: Background To compare the clinical outcomes of patients receiving short course (SC) or prolonged course (PC) of antifungal therapy for uncomplicated Candida bloodstream infections (BSI). Methods All episodes of uncomplicated Candida BSI from 1 September 2018 to 31 August 2020 were reviewed. We compared the primary (all cause 90-day mortality) and secondary study endpoints (1-year recurrent Candida BSI and all-cause 1-year-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…As for candidemia, adherence to international recommendations outlined in the EQUAL Candida score, representing a management bundle, is an independent predictor of survival [18]. Nevertheless, the boundary between complicated and uncomplicated forms is somewhat porous [3]; although, the absence of metastatic foci and of deep-seated candidiasis may be considered as a marker of a not-complicated infection [19].…”
Section: Catheter-related Bloodstream Infections (Crbsis) Complicated...mentioning
confidence: 99%
See 1 more Smart Citation
“…As for candidemia, adherence to international recommendations outlined in the EQUAL Candida score, representing a management bundle, is an independent predictor of survival [18]. Nevertheless, the boundary between complicated and uncomplicated forms is somewhat porous [3]; although, the absence of metastatic foci and of deep-seated candidiasis may be considered as a marker of a not-complicated infection [19].…”
Section: Catheter-related Bloodstream Infections (Crbsis) Complicated...mentioning
confidence: 99%
“…Bloodstream infections (BSIs) represent no exception, and for instance, there is a growing body of evidence showing no significant difference in clinical outcomes comparing patients with uncomplicated Gram-negative BSI allocated to receive 7 days and the ones assigned to receive 14 days in randomized clinical trials (RCTs) [2]. Even in uncomplicated candidemia some authors advocated a shorter course than the usual 14 days after the first negative follow-up blood culture (FUBC) relying on a retrospective study [3]. From analogous evidence, other researchers suggested that in uncomplicated Staphyloccocus aureus BSI, namely the paradigmatic form of bacteremia with metastatic potential, less than 14 days of therapy may suffice according to real-world evidence (RWE) data [4].…”
Section: Introductionmentioning
confidence: 99%